The use of blanket guarantees in banking crises - Laeven, Luc (IMF working paper ;, 2008)
In episodes of significant banking distress or perceived systemic risk to the financial system, policymakers have often opted for issuing blanket guarantees on bank liabilities to stop or avoid widespread bank runs. In theory, blanket guarantees can prevent bank runs if they are credible. However, guarantee could add substantial fiscal costs to bank restructuring programs and may increase moral hazard going forward. Using a sample of 42 episodes of banking crises, this paper finds that blanket guarantees are successful in reducing liquidity pressures on banks arising from deposit withdrawals. However, banks' foreign liabilities appear virtually irresponsive to blanket guarantees. Furthermore, guarantees tend to be fiscally costly, though this positive association arises in large part because guarantees tend to be employed in conjunction with extensive liquidity support and when crises are severe.